Thermal degradation kinetics of monomeric anthocyanins, colour changes and storage effect in elderberry juices - Busso Casati, Carolina (2015)
Fil: Busso Casati, Carolina. Pontificia Universidad Católica Argentina. Facultad de Ciencias Agrarias; Argentina